In-situ SAXS/WAXS investigations of ureidopyrimidinone functionalized semi-crystalline poly(ethylene-co-butylene) supramolecular polymers. (16th July 2021) - Louati, Maroua; Tahon, Jean-François; Fournier, David; Stoclet, Gregory; Aloise, Stéphane; Takao, Marumi; Takeshita, Michinori; Lefebvre, Jean-Marc; Barrau, Sophie
Abstract: The structural evolution as a function of temperature of a supramolecular copolymer assembly based on multiple hydrogen bonds has been investigated. Ureidopyrimidinone functionalized semi-crystalline poly(ethylene-co-butylene) (PEB-(L-UPy)2 ) has been characterized by means of in situ WAXS and SAXS experiments. The crystallinity and the nature of crystal forms are associated to the ethylene sequences. Special attention has been paid to the impact of the hydrogen bonding network on the structural arrangements, by comparison to the unfunctionalized PEB. The presence of crystalline domains of in-plane arrangement between neighboring UPy dimers is detected by WAXS up to 80 °C. The SAXS data reflect the presence of L-UPy aggregates stable on the whole temperature range. The correlation of these UPy-based aggregates is effective until the PEB crystal melting temperature (Tm). Beyond Tm, the increase of the macromolecular mobility reduce the number of domains in interaction and, in consequence, implies a decorrelation of the aggregates. Graphical abstract: Image 1 Highlights: Synthesis of ureidopyrimidinone functionalized semi-crystalline poly(ethylene-co-butylene). WAXS structural characterization of the copolymer crystal forms. Combined SAXS/WAXS investigation of the multi-scale arrangements of the supramolecular assembly as a function of temperature.